PENGARUH PEMBAGIAN KERJA DAN KEPEMIMPINAN TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. HARMONI PANCA UTAMA DI TENGGARONG SEBERANG - Ernawati; Johansyah; Hendra (SEKOLAH TINGGI ILMU EKONOMI TENGGARONG, 2023)
Observations show that the division of work still overlaps or is uneven between one employee and another, the workload given is sometimes very heavy to carry out because it does not match the abilities of the employee concerned, leaders are less able to provide clear and directed guidance, leaders are also sometimes unfair to employees. which often puts some employees on a pedestal, causing jealousy among other employees. There are also employees who complain that the work facilities available at this company are still lacking. It should be PT. Harmoni Panca Utama must be able to pay close attention to the current conditions of problems in the company, to find solutions. If there is no further treatment, this will affect employee work productivity so that their daily activities will be disrupted. The aim of this research is to determine the effect of division of work and leadership on job satisfaction at PT. Harmoni Panca Utama in Tenggarong opposite. The sample in this study consisted of 32 respondents. The analytical tools used to analyze are multiple regression and hypothesis testing using the f and uii t tests. The research results show that together the division of work and leadership have a significant influence on job satisfaction at PT. Panca Utama in Tenggarong Seberang and each of these variables also has a significant influence.